(untitled) (Journal of Hama University, 2026)
The research aimed to identify the level of psychological adjustment among mothers of children with mental handicap and mothers of children with autism spectrum disorder in the city of Lattakia, also identifies differences in psychological adjustment among sample members according to the type of disability and severity of disability. The researcher adopted the descriptive approach, and the research tool is the psychological adjustment questionnaire prepared by the researcher. The research community consisted of all mothers of children with mental handicap and autism spectrum disorder in the city of Lattakia. The research sample consisted of (40) mothers, including (22) mothers of children with mental handicap and (18) mothers of children with autism spectrum disorder who visit the Women’s Support and Empowerment Center in the city of Lattakia. They were drawn using a simple random method. The results indicated that the largest percentage of mothers of children with mental handicap (55%) and the largest percentage of mothers of children with autism spectrum disorder (50%) have a low level of psychological adjustment, as shown by There was no difference in the psychological adjustment of mothers according to the type of disability (mental handicap, autism spectrum disorder), and there were no differences in the psychological adjustment of mothers according to the severity of the disability (mild, moderate, severe).